2013
DOI: 10.4028/www.scientific.net/amr.671-674.10
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bearing Capacity for Quicklime Compaction Pile Composite Foundation

Abstract: In the collapsible loess of Midwest China, quicklime compaction pile composite foundation has been widely used in practical engineering. Firstly,the calculation method of quicklime compaction pile composite foundation is analyzed; then the influencing factors of bearing capacity for quicklime compaction pile composite foundation was researched on the basis of the character about soil compaction effect between piles with the quicklime expanding when absorbing water from the soil; lastly, the calculation method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…is process will reach equilibrium when the dry Ca(OH) 2 absorbs a certain amount of water. e previous study indicated that an appreciable amount of water is absorbed during this process [20].…”
Section: Reinforcement Mechanisms Ofmentioning
confidence: 94%
“…is process will reach equilibrium when the dry Ca(OH) 2 absorbs a certain amount of water. e previous study indicated that an appreciable amount of water is absorbed during this process [20].…”
Section: Reinforcement Mechanisms Ofmentioning
confidence: 94%